An Experimental Study on the Thermal Efficiency of a Passive Solar Air Collector - FIUK, Jacek Jan; DUTKOWSKI, Krzysztof; PIĄTKOWSKI, Piotr (Engineering Transactions, 2017)
This paper presents the results of an experimental investigation on a prototype flat passive air solar collector. The collector consists of an aluminum casing, transparent cover, air inlet and outlet channels and a flat absorber plate mounted inside the casing. The design is unique because the cover is made of transparent cellular polycarbonate sheet, a material whose application to passive solar collectors has not been extensively researched. The cover is 5 mm thick. The airflow through the collector is driven by natural convection. The study was performed on a laboratory set-up consisting of vertically mounted collector, external source of thermal radiation in the form of infrared lamps, measurement equipment and data acquisition system. The tests were performed for a range of irradiance $G$ = 0–540 W/m$^2$. The following parameters were determined: absorber surface temperature, air temperature increase, collector heat output and efficiency. Comparing the obtained results to the available data on conventional glass-covered designs has shown that the optical performance of polycarbonate cover is lower. However, in terms of thermal efficiency this is compensated by good insulation. The measurements for the maximum attainable irradiance of $G_{\max}$ = 540 W/m$^2$ are as follows: the mean air velocity at inlet $w$ = 1.1 m/s, the volumetric flow rate of air $\dot{V}$ = 30 m$^3$/h, and the corresponding heat output and thermal efficiency $Q$ = 386 W and $η$ = 36%, respectively.